Analysis of the Influence of Tourist Visits and Hotel Occupancy Rate on Labor Absorption in West Nusa Tenggara Province - Shofyah Syafinah; Emi Salmah; Masrun Masrun (West Science Journal Economic and Entrepreneurship, 2024)
This study aims to analyze "The influence of tourist visits and hotel occupancy rates on labor absorption in West Nusa Tenggara Province". The type of research used in this study is quantitative research with a descriptive approach. The type of data used in the study is time series data. The data was processed using the SPSS application using the Multiple Liniear Regression analysis method. The results of this study show that simultaneously the independent variables of tourist visits (X1) and hotel occupancy rate (X2) do not have a significant effect on the dependent variable, namely labor absorption (Y) even though it has a strong correlation. The results of the partial test show that Tourist Visits and Hotel Occupancy Rate have no significant effect on Labor Absorption in the hospitality sector. The results of multiple regression testing of the data in this study recommend the regression equation: Y = 2700.556 + 0.002 X1 + 0.001 X2. The constant value is 2700.556, the coefficient X1 is 0.002 and the hotel occupancy rate is 0.001.